MORPHOLOGICAL VARIATION OF THE SILVER WHITING Sillago sihama Forskal IN INDONESIA - Sulistiono Sulistiono; Yuniar Yuniar; Seiichi Watanabe; Masashi Yokota (Jurnal Iktiologi Indonesia, 2002)
Study on the morphological variation of the silver whiting (Sillago sihama) was conducted using samples collected in some locations in Indonesia (Ujung Pangkah-East Java Province, Segara Anakan-Central Java Province, Arafuru Sea-Maluku Province and Dumai-Riau Province) using gill net and mini trawl from 1995 to 1998. Some meristics and morphometries characters were observed to estimate population characteristics. Some meristics characters (pectoral rays, scales at lateral line and scales at caudal peduncle), and some morphometries characters (the body depth, caudal peduncle length, predorsal length, length of dorsal fin base 2, length of pectoral fin, length of pelvic fin, head length, head width, snout length, suborbital width, orbit to pre opercle angle and eye diameter-devided by total length) were important characters to investigate local population. Using multivariate analysis, they could not show a significations among local population of S. sihama, therefore it seems signification in the local population of Arafuru Sea group and others.ABSTRAKPengamatan terhadap variasi morfologi ikan putih (Sillago sihama) di Indonesia dilakukan dengan menggunakan sampel ikan dari beberapa lokasi (Ujung Pangkah-Jawa Timur, Segara Anakan-Jawa Tengah, Laut Arafuru-Maluku dan Dumai-Propinsi Riau) dengan menggunakan jaring insang dan mini trawl dari tahun 1995 sampai 1998. Beberapa parameter meristik dan morfometrik dilakukan pengamatannya untuk mengetahui karakter populasi. Beberapa karakter meristik (panjang jari-jari sirip dada, sisik pada linea lateralis dan sisik pada batang ekor), dan karakter morfometrik (tinggi badan, panjang batang ekor, panjang depan sirip punggung, panjang dasar sirip punggung ke 2, panjang sirip dada, panjang sirip perut, panjang kepala, lebar kepala, panjang hidung, lebar antar mata, panjang antara mata dan tutp insang depan, lebar mata yang dibagi dengan panjang total) merupakan karakter yang penting dalam pengamatan populasi lokal. Dengan menggunakan analisis multivariate, belum menampakkan perbedaannya antar populasi S. sihama, namun demikian terdapat perbedaan antara kelompok populasi Laut Arafuru dibandingkan dengan yang lain.